Development and Management of the Higher Education Quality System - Kučinskienė, Ramutė; Kučinskas, Vytautas (Acta Paedagogica Vilnensia, 2005)
The development of modem quality assessment systems in the higher education institutions in Lithuania is perceived as one of the cardinal imperatives. Solid base for quality assessment and management system should be provided by the sciences of management and education management. First of all, key concepts (quality, quality management) are specified more precisely in the article, having in mind particularities of educational organizations. Colleges are quiet new institutions of non-university higher education in Lithuania. Achievements in the colleges’ quality systems development and management are analysed highlighting main questions: what persons had been developing quality system in colleges, what standards had been used, what system of quality management had been chosen, what are further perspectives of study quality system’s development. Opinions of all interested parts, participating in the quality system’s development (students, administration, teachers, employers) were analysed. The main generalizations made at the end of the article are: l) the main dimensions of the study quality system are mission and vision of the organization, and management of personnel, resources, finance, services, risk, and strategies. 2) Development of the study quality system should be based on the joint general dimensions and standards, avoiding inadequate and unqualified interpretation or personal visions. 3) Experience of Klaipeda Maritime College in application of requirements of the international standard ISO 9001: 2000 is positive and beneficial for other higher education institutions. 4) Development of study quality system depends on the competencies of personnel. Not every teacher has suitable competence, and special training is needed for most. 5) Quality groups from universities and colleges should cooperate. More active participation is requested from employers.